Emerging Infectious Diseases - Jorge R. Rey (EDIS)
ENY-740, a 10-page illustrated fact sheet by Jorge R. Rey, describes what emerging infectious diseases are, gives some examples, some of the common causes for emergence or re-emergence of the diseases. Includes references. Published by the UF Department of Entomology and Nematology, May 2007.